The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/smtd.201900474
|View full text |Cite
|
Sign up to set email alerts
|

Is It Appropriate to Use the Nafion Membrane in Electrocatalytic N2 Reduction?

Abstract: The electrocatalytic N2 reduction reaction (ENRR) to ammonia has attracted much attention due to the mild operating conditions, in which the Nafion membrane is generally adopted to separate the ammonia from the anode products. However, it has been mentioned that the Nafion membrane allows ammonia to pass through and traps the ammonia to some extent, but powerful confirmation experiments and effective solutions are still lacking. Herein, it is experimentally confirmed that the use of the Nafion membrane in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 22 publications
4
55
1
Order By: Relevance
“…In 2018, Tao and co‐worker used density functional theory calculations to show that the Ru sites with oxygen vacancies are beneficial for N 2 adsorption . It is worth noting that Tao also pointed out that the addition of ZrO 2 increased the Faraday efficiency, which was due to the inhibitory effect of ZrO 2 on the HER, which is consistent with the calculation results of Nørskov …”
Section: Strategy To Improve the Nrrsupporting
confidence: 87%
See 2 more Smart Citations
“…In 2018, Tao and co‐worker used density functional theory calculations to show that the Ru sites with oxygen vacancies are beneficial for N 2 adsorption . It is worth noting that Tao also pointed out that the addition of ZrO 2 increased the Faraday efficiency, which was due to the inhibitory effect of ZrO 2 on the HER, which is consistent with the calculation results of Nørskov …”
Section: Strategy To Improve the Nrrsupporting
confidence: 87%
“…For the use of membrane, Qiu et al. confirm that Nafion membrane is inappropriate for N 2 reduction reaction because it allows NH 3 to pass through, and traps NH 3 to some extent …”
Section: Strategy To Improve the Nrrmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the possible physical and chemical interactions between the Nafion membrane and the redox products should be carefully avoided when designing the photoelectrochemical reactors. Very recently, Ren et al reported that the Nafion membrane allows ammonia to pass through and absorbs the ammonia to some extent, which may cause a measurement error up to around 30% . Similar considerations should be taken into the design of photoelectrochemical reactors for CO 2 conversion and pollutant degradation processes in the future.…”
Section: Limitations Potential Solutions and Future Outlookmentioning
confidence: 99%
“…[1,2,9] Ren and co-workers have concluded that the use of Nafion membranes in NRR experiments may be inappropriate, as ammonium can pass through the membrane, be adsorbed on the membrane or, even, interact with it, which is unfavorable for reliable and reproducible quantification of the product. [10] Although long-term application of Nafion (7-10 days) is not suitable owing to loss of conductivity, Nafion membranes are nevertheless widely used in short term (ca. 2 h) NRR experiments today and deserve further investigation on pretreatment protocols to obtain as reliable data as possible.…”
mentioning
confidence: 99%